The family book - Parr, Todd (2020)
This title features a variety of families from big and small, to some with only one parent or some with two moms and dads - but all alike in some ways and special no matter what. Aligned to Common Core standards and correlated to state standards.
"The family book celebrates all kinds of families and shows how each is special in its own way" -- Page [4] of cover.
3-7
Keywords: Families -- Juvenile literature; Individuality -- Juvenile literature; Families; Individuality; Picture books for children; Picture books for children; Juvenile works; Picture books; Picture books